Oral health restablishment of a patient with smoking habit and addiction to psychotropic substances: a case report - Lugo Vásquez, Paula Valentina (2024)
Introduction: Smoking and consuming illicit drugs have a negative impact on different areas of the person involved with these habits. As well, it has been described a number of consequences on the oral health such as halitosis and caries but even periodontal disease and oral cancer. The objective of this case report is to make evident the effects that a patient with smoking habit and addiction to psychoactive substances shows on the stomatological system and be able to recover the oral health through the application of a integral treatment. Materials and methods: A 51 year old male patient comes to a odontologic consultation with pain and discomfort on the oral cavity. He reffers consuming a cigarrette pack daily and having addiction to cocaine and crack. Results: The presence of oral diseases and stomatological conditions related to the habit of smoking and consuming cocaine were observed. A treatment that included different medical en dental especialties was applied on the patient. Conclusion: It was possible to verified the effects of smoking and consuming psycoactive substances, and restablish the oral health of a patient with these harmful habits, recovering stomatological functions, aestethics and improving his life quality.